Simulasi Dampak Kebijakan Moneter terhadap Perekonomian dan Emisi CO2 Per Kapita di Indonesia - Ningrum, Icha Wahyu Kusuma; Agustini, Peni; Nabilah, Yasmin Nur Alya (Politeknik Statistika STIS, 2024)
In running an economy, energy is needed as an input for the production process. However, energy needs are still dominated by energy from fossils that produce CO2 emissions. CO2 emissions can cause global climate change where the United Nations (UN) is struggling to combat climate change and its impacts through the 13th Sustainable Development Goals. This study aims to examine the simultaneous relationship between gross domestic product, CO2 emissions, and gross fixed capital formation in Indonesia and the variables that influence the three indicators using a simultaneous equation model with the two stage least squares (2SLS) method. In addition, a simulation will be carried out when an intervention is made on monetary policy against the three indicators. As a result, the scenario that can improve the economy and CO₂ emissions per capita is by lowering interest rates. While the scenario that can reduce the economy and CO2 emissions per capita is by raising interest rates.